2018
DOI: 10.1136/bmjresp-2017-000266
|View full text |Cite
|
Sign up to set email alerts
|

BTS guideline for the investigation and management of malignant pleural mesothelioma

Abstract: The full guideline for the investigation and management of malignant pleural mesothelioma is published in Thorax. The following is a summary of the recommendations and good practice points. The sections referred to in the summary refer to the full guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 2 publications
(1 reference statement)
0
24
0
3
Order By: Relevance
“…There was no difference in quality of life, chest pain, analgesia requirement, or overall development of procedure tract metastasis between groups. Major international guidelines now recommend against the routine use of prophylactic irradiation [29, 43, 44]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference in quality of life, chest pain, analgesia requirement, or overall development of procedure tract metastasis between groups. Major international guidelines now recommend against the routine use of prophylactic irradiation [29, 43, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…Although this was a single-centered study, we feel that our results are generalizable to that of other tertiary-care centers managing MPM. Patients at our institution are treated according to internationally recognized standards and guidelines for the management of MPM [29, 43]. Our results, however, cannot be applied to non-MPM patients as the incidence of CTM is known to be higher in patients with MPM compared to other malignancies [21].…”
Section: Discussionmentioning
confidence: 99%
“…The British Thoracic Society guidelines recommend patients should be offered 3 to 4 monthly follow-up appointments with an oncologist, respiratory physician, or specialist nurse according to their current treatment plan. 75 Progression-free survival, if reported, is usually longer after EPP in comparison to P/D, and especially the local recurrence rates are higher in P/D groups. 38 The most recent comprehensive meta-analysis was conducted to compare if P/D or EPP is more beneficial to MPM patients.…”
Section: Epp and P/d -Comparisonmentioning
confidence: 92%
“…Depending on the PET endpoint used some studies have shown a role in baseline prognostication but no ability to monitor disease (6). The recent BTS guidelines on mesothelioma do not recommend the routine use of PET-CT except in patients "where excluding distant metastases will change management" (12). A potential future direction of study is the assessment of PET as a prognostic marker for lung cancer in patients with pleural effusions who might otherwise have been amenable for surgical resection.…”
Section: Editorialmentioning
confidence: 99%